Management of silver point retrieval for root canal retreatment: a case report / Afzan Adilah Ayoub and Gary Shun-Pan Cheung - Ayoub, Afzan Adilah; Cheung, Gary Shun-Pan (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
The historical importance of the solid core material is decreasing. When greater, more precise preparation of the canal space was not possible due to inferior metallurgy and instrument design, it was frequently utilized in the past. Silver points were machined with a circular cross section and more frequently than not went into oval than round canals. Long-term success rates might not be as great, but some cases may defy the odds. The prognosis after treatment and follow up by phone five years after the completion of treatment. A 46-years-old Chinese female was referred from a general private practitioner for the endodontic management of 36. The tooth had been endodontically treated 30 years before; subsequently the patient complained of occasionally mild discomfort that last a few second without any stimulating factors at the lower left molar. Radiographic finding revealed that the tooth had been treated with silver points and associated with periapical radiolucency. Non-surgical root canal retreatment was performed for the tooth. Conclusions: Due to the nature of partially removal silver points, even though the prognosis is guarded at the time of obturation. After five years, it was considered favourable although it was extracted due to fracture.